Persaingan politik Melayu di Semenanjung Malaysia, 1978-2013 / Mohd Sabri Md Nor - Mohd Sabri , Md Nor (2016)
This study aims at examining the history of political rivalry between United Malays National Organisation (UMNO) and Parti Islam Se-Malaysia (PAS). This study focuses on the Malay political rivalry in reinforcing Islam, power and leadership struggle and unity issues during 1978 to 2013. The year 1978 was chosen since it was the year PAS returned as the main rival for UMNO after being dismissed from Barisan Nasional in December 1977. This was due to the reluctance of PAS to support Kelantan Emergency Bill following the crisis involving Muhammad Nasir position as Chief Minister of Kelantan. The crisis resulted in a split in PAS and PAS influence began to decline after suffering major defeats in the GE-5 (1978) when confronting UMNO and BERJASA (PAS splinter party). This had caused PAS lost its domination over Kelantan. The emergence of Islamic revivalism since the early 1970s resulted in a stiff competition between UMNO and PAS for the empowerment of Islamic agenda through various programs. The rivalry between UMNO and PAS, especially in the 12th (2008) and the 13th general election (2013) was perceived as more challenging with the declining support for UMNO and non-Malay votes became more dominant. During this period (1978-2013), Malay political rivalry is seen as dynamic, challenging and significant to gain public support. This study used qualitative approach involving interviews and library research. In addition to the interview data, the study also examined documents such as speeches, annual reports and election manifesto in order to explore issues in and patterns of the rivalry. Generally, the study found that the main element in the Malay political rivalry was the issues of Islam followed by the issues of Malay. The prolonged Malay political rivalry is driven by differences in views and opinions of the political leaders that emerged from diverse school of thought. Failure to manage these differences has resulted in tensions that eventually led to hostility. Hostility between UMNO and PAS also involved the issue of religion and aqidah such as, apostatizing, hudud and Islamic country. The political rivalry led to a split among their followers to the extend having separate imams during prayer, separate cemetery and shattered family relationships due to differences in political ideologies. The study found that a suggestion for a coalition between UMNO and PAS is unfeasible. More inclusive type of unity that involves the ruling and opposition parties needs to be promoted with the Malay unity as the pillar. Even though the rivalry between UMNO and PAS is perceived as almost impossible for the two parties to reunite, it does not prevent them to discuss about Malay unity. However unity in term of collaboration between the two parties has not yet to materialize since PAS is seen as too cautious in accepting UMNO’s offer to avoid the recurrence of 1977 event.